The Origins of State Intervention in the Control of Juvenile Delinquency: The Nebraska Experience - Massey, James L. (1976)
The pages that follow trace the origins of Nebraska's experience in official state intervention in the control of juvenile delinquency. The focus is on the developmental stages of the Nebraska juvenile justice system, and is designed to inform the reader about the foundation upon which this system has been built, as well as the assumptions that were implicit in this activity. The early chapters provide a brief overview of efforts to define and prevent juvenile delinquency from colonial times to just prior to the onset of the American Civil War. It was in this period that some forms of youthful misbehavior gradually came to be dealt with by a state supported system of control and ceased to fall exclusively under the auspices of traditional family discipline. After the Civil War a movement began which consolidated on a national scale correctional efforts which had previously been the concern of individual states acting in relative isolation. This movement will be traced through the activities of the National Conference of Charities and Correction, which during the last quarter of the nineteenth century was unquestionably an organization of prime influence in virtually all areas of child-saving